Extended‐release methylphenidate for treatment of amphetamine/methamphetamine dependence: a randomized, double‐blind, placebo‐controlled trial. (1st March 2013) - Miles, S. Wayne; Sheridan, Janie; Russell, Bruce; Kydd, Rob; Wheeler, Amanda; Walters, Carina; Gamble, Greg; Hardley, Peta; Jensen, Maree; Kuoppasalmi, Kimmo; Tuomola, Pekka; Föhr, Jaana; et al.
Abstract Aims To assess the efficacy of methylphenidate as a substitution therapy for amphetamine/methamphetamine dependence in Finland and New Zealand. Design Parallel‐group, double‐blind, randomized placebo‐controlled trial. Setting Out‐patient care. Participants Amphetamine‐/methamphetamine‐dependent, aged 16–65 years. Measurements The primary outcome measure was presence/absence of amphetamine/methamphetamine in urine samples collected twice weekly. Secondary measures included treatment adherence, alterations in craving scores and self‐reported use. Primary analysis was by intention‐to‐treat (ITT). The study drug, methylphenidate (as Concerta®), was up‐titrated over 2 weeks to a maximum dose of 54 mg daily and continued for a further 20 weeks. Doses were given under daily supervision at the clinics. Findings Seventy‐nine participants were randomized (40 methylphenidate; 39 placebo); 76 received allocated treatment and 27 completed the trial. ITT analysis (n = 78) showed no statistically significant difference in the percentage of positive urines between the methylphenidate and placebo arms (odds ratio: 0.95, 95% confidence interval: 0.83–1.08). However, there was a significant difference (P < 0.05) between the active and placebo arms in retention, the placebo arm displaying a significantly lower retention from 6 weeks that persisted until the end of the trial. Conclusions The trial failed to replicate earlier findings suggesting that methylphenidate was superior to placebo. The low retention rate confounded the ability to draw firm conclusions about efficacy. The higher retention rate was observed in the methylphenidate arm. Any replication of this work would need to consider alternatives to the rigid clinic attendance criteria, and consider an increased dose.